Labour at the Lakehead: Ethnicity, Socialism, and Politics, 1900-35 - Beaulieu, Michel S. (UBC Press, 2011)
In the early twentieth century, the Canadian Lakehead was known as a breeding ground for revolution, a place where harsh conditions in dockyards, lumber mills, and railway yards drove immigrants into radical labour politics. This intensely engaging history reasserts Northwestern Ontario's rightful reputation as a birthplace of leftism in Canada by exposing the conditions that gave rise to an array of left-wing organizations, including the Communist Party, the One Big Union, and the Industrial Workers of the World. Yet, as Michel Beaulieu shows, the circumstances and actions of Lakehead labour, especially those related to ideology, ethnicity, and personality were complex; they simultaneously empowered and fettered workers in their struggles against the shackles of capitalism. Cultural ties helped bring left-wing ideas to Canada but, as each group developed a distinctive vocabulary of socialism, Anglo-Celtic workers defended their privileges against Finns, Ukrainians, and Italians. At the Lakehead, ethnic difference often outweighed class solidarity - at the cost of a stronger labour movement for Canada. --Publisher's description
Keywords: 20th century; Ethnic relations; History; Labor movement; Labor unions; Ontario; Politics and government; Social conditions; Thunder Bay, Ont.

The Lakehead & Canada’s First Social Democratic Party: - Beaulieu, Michel S (Thunder Bay Historical Museum Society Papers and Records, 2011)
During the last two days of December in 1911 the Finnish Labour Temple in Port Arthur, Ontario, was the scene of one of the most significant events in both Canadian and regional political history before the First World War. Chosen for its geographic position, the temple hosted a pan-national gathering of socialists who, in an attempt to unite the Canadian left, established Canada’s first social democratic party, the Social Democratic Party of Canada (SDPC). The goal of the SDPC was to educate the workers of Canada to consciousness of their class position in society, their economic servitude to the owners of capital, and to organize them into a political party to seize the reins of government and transform all capitalist property into the collective property of the working class. Its activity during the next decade would have a profound influence on both the various manifestations of socialism regionally and nationally over the next century and on mainstream Canadian social politics. However, the hundredth anniversary of its establishment has gone unnoticed by political and labour historians. Part of the reason rests with the simply fact that, although many works mention and even briefly discuss the SDPC, no full-length study has yet been written. In an attempt to rectify this situation, this paper provides an overview of its actions and activities at the Lakehead,between 1911 and 1918. --Introduction

Hard Work Conquers All: Building the Finnish Community in Canada - Harpelle, Ronald N.; Ratz, David K.; Beaulieu, Michel S. (UBC Press, 2018)
Above the entrance to the Finnish Labour Temple, in what was once Port Arthur in northern Ontario, is the motto labor omnia vincit – “hard work conquers all.” Since 1910, these words have reflected the dedication of the Finnish community in Canada. This book is a social history of Finnish immigration and community building in Canada during the twentieth century. The first Finns to arrive ranged from conservative churchgoers to radical socialists, reflecting the ideologies that divided their homeland. After the First World War, left-wing Finns fled persecution; following the Second World War, Finns sought the economic security that Canada offered. Each new wave of immigration imbued the relationship between people, homeland, and host country with the politics, ideologies, and cultural expressions of its time. The story of Finns in Canada dovetails with the larger literature on immigration and enriches the history of socialism and ethnic repression in this country. The insightful essays in Hard Work Conquers All explore the nuanced cultural identities of Finnish Canadians, their continued ties to Finland, intergenerational cultural transfer, and the community’s connections with socialism and labour movements. This is a fresh interpretation of the successive waves of Finnish immigration and their influence on Canadian politics and society. --Publisher's description
Keywords: 1900-1999; Canada; Canadiens d'origine finlandaise; Canadiens d'origine finlandaise Conditions sociales 20e siècle; Canadiens d'origine finlandaise Conditions économiques 20e siècle; Canadiens d'origine finlandaise Mœurs et coutumes 20e siècle; Finnish Canadians; Finnish Canadians Economic conditions 20th century; Finnish Canadians Social conditions 20th century; Finnish Canadians Social life and customs 20th century; Finns; Finns Canada; Finns Canada Economic conditions 20th century; Finns Canada Social conditions 20th century; Finns Canada Social life and customs 20th century; Finns Social conditions; Finns Social life and customs